2019
DOI: 10.1111/ajd.13211
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic review and Meta‐Analysis of the survival and clinicopathological features of p63 expression in Merkel cell carcinoma

Abstract: Merkel cell carcinoma (MCC) is a rare skin tumour of neuroendocrine origin with aggressive behaviour. The aims of this study were to investigate the association of p63 + MCC with clinicopathological features and to estimate survival through a systematic review and meta-analysis. A comprehensive search of PubMed, Embase, Scopus and Virtual Health Library following the PRISMA guidelines was conducted on September 2017. DerSimonian and Lard random-effects models were used to calculate survivalweighted means and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…10 The transcription factor p63, a member of the p53 family that plays a role in the UV-induced pathogenesis of MCC, has been associated with a poor prognosis. 11,12 MCPyV positive tumors are associated with a more favorable prognosis and confer a protective factor for the expression of p63. 6,11,12 The IHC profile of our patient is positive for MCPyV large T-cell antigen and negative for p63, reflecting a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The transcription factor p63, a member of the p53 family that plays a role in the UV-induced pathogenesis of MCC, has been associated with a poor prognosis. 11,12 MCPyV positive tumors are associated with a more favorable prognosis and confer a protective factor for the expression of p63. 6,11,12 The IHC profile of our patient is positive for MCPyV large T-cell antigen and negative for p63, reflecting a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 MCPyV positive tumors are associated with a more favorable prognosis and confer a protective factor for the expression of p63. 6,11,12 The IHC profile of our patient is positive for MCPyV large T-cell antigen and negative for p63, reflecting a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…While the need to record the p63 status of MCCs in routine practice is arguable, some authors favor documentation of this parameter in the interests of further data generation and additional analysis. Of importance, minimal staining for p63 (ie, Hall's score ≥ 10, as described previously 79 ) represents positivity; hence its interpretation should emulate that of estrogen receptor status in breast cancer 77,80 …”
Section: Prognosismentioning
confidence: 97%
“…Expression of p63 by MCC cells, as an indicator of cell cycle modulation rather than lineage, has been linked to a poor outcome by most, but not all, investigators 70‐78 . A recent systematic review analyzing the cumulative evidence to date has shown this parameter to have significant adverse prognostic implications and to be associated with a MCPyV‐negative status 79 . Conflicting data exist as to whether p63 is an independent prognostic variable in MCC 71,75 hence further work is required to resolve this matter.…”
Section: Prognosismentioning
confidence: 99%
“…Whereas MCCs negative for CK20 and MCPyV were previously thought to behave more aggressively, recent data on MCPyV is mixed, demonstrating that both virus-positive and virus-negative tumors can have an aggressive course (Asioli et al, 2007;Coursaget et al, 2013;Moshiri et al, 2017). MCCs with increased expression of p63 are associated with an increased risk of mortality, but p63 is not used in clinical practice as a recognized biomarker because it does not predict survival when stage is taken into consideration (Portilla et al, 2020;Stetsenko et al, 2013). MCCs are negative for TTF-1 and S-100, which differentiate between lung carcinoma and melanoma (TTF-1 is related to lung carcinoma and S-100 with melanoma).…”
Section: Detailed Answersmentioning
confidence: 99%